Ventricular Septal Perforation after Biventricular Takotsubo Cardiomyopathy Successfully Repaired with an Amplatzer Device: First Report in the Literature - Alfredo E. Rodríguez; Carlos Fernandez-Pereira; Juan Mieres; Diego Ascarrunz; Eduardo Gabe; Alfredo Matías Rodríguez-Granillo; Romina Frattini; Pablo Stuzbach (Case Reports in Cardiology)
A 79-year-old female was admitted with sudden onset dyspnea, mild oppressive chest pain, and severe anxiety disorder. Patient had history of hypertension, dyslipidemia, smoking, and chronic obstructive pulmonary disease. On admission blood pressure was 160/90 and heart rate was 130 bpm. Transthoracic echocardiography (TE) and contrast tomography showed a thin septum with an abnormal left and right ventricular contraction with an “apical ballooning” pattern and mild increase of cardiac enzymes. At the 4th day of admission, the patient presented symptoms and signs of congestive heart failure and developed cardiogenic shock. EKG showed an inversion of T waves in all precordial leads. In a new TE, a ventricular septal perforation (VSP) in the apical portion of the septum was seen. Coronary angiogram showed angiographically “normal” coronary arteries. With a diagnosis of VSP in takotsubo cardiomyopathy, a percutaneous procedure to repair the VSP was performed 11 days after admission. The VSP was closed with an Amplatzer device. TE performed 24 hours after showed significant improvement of ventricular function and good apposition of the Amplatzer device. Three days later she was discharged from the hospital. To our knowledge, this is the first reported case of a VSP in a TCM repaired percutaneously with an occluder device.